Analisis Diksi dan Makna Pada Puisi berjudul “Antara Gelap dan Terang Manusia” Karya Ariffin Noor Hasby - Nadia Halima Putri; Jumadi Jumadi; Dwi Wahyu Candra Dewi (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
The poem "Antara Gelap dan Terang Manusia" by Ariffin Noor Hasby in the book Salawat Laut aims to analyze the diski and meaning of the poem. This poem explains the meaning of each word used by the author has a certain meaning in which the reader understands the intention and purpose conveyed by the author. The method in this study is qualitative and data collection techniques using literature techniques by understanding the content of the poem. Through the analysis of the poem "Between Darkness and Human Light" by Ariffin Noor Hasby, the diction chosen by the author has a deep meaning, namely telling the story of a person's spiritual journey in searching for the meaning of life in the midst of the complexity of the world, such as darkness and light, heart and mind, sin and forgiveness. This journey is described as an attempt to find love, truth, and inner peace. This poem describes the beauty, emotion, and complexity of the relationship. The repetition of the phrase "Between darkness and human light" at the beginning of each verse emphasizes that this is a universal human condition that continues to be in a struggle between good and evil, between enlightenment and spiritual darkness.